2006
DOI: 10.1111/j.1440-1738.2006.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic facies and geochemical aspects in Neogene neritic sediments of the Takafu syncline area of central Japan: Paleoenvironmental and sedimentological reconstructions

Abstract: Organic petrological observations of kerogen macerals and organic geochemical analyses of carbon isotopes of kerogen macerals and biomarkers were conducted on Neogene neritic sediments of the Takafu syncline area of central Japan. The Senmi, Sakainomiya and Lower Shigarami Formations in that area were deposited at the neritic provinces on the southern edge of the paleo-Japan Sea during the Late Miocene to Early Pliocene. Sedimentary organic matter in these formations was almost terrigenous in origin. Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…On the other hand, the lowest values of H/C in the samples that have high NFA (layers 24e-2 and 24e-3) supports that the NFA is terrigenous woody organic matter origin. Sawada (2006) confirmed that the vitrinite (wood) and NFA-rich fraction of kerogen had a relatively low H/C ratio, which agrees with the H/C results of this study. Fig.…”
Section: Elemental and Pyrolysis-gc Data Of Kerogensupporting
confidence: 82%
See 4 more Smart Citations
“…On the other hand, the lowest values of H/C in the samples that have high NFA (layers 24e-2 and 24e-3) supports that the NFA is terrigenous woody organic matter origin. Sawada (2006) confirmed that the vitrinite (wood) and NFA-rich fraction of kerogen had a relatively low H/C ratio, which agrees with the H/C results of this study. Fig.…”
Section: Elemental and Pyrolysis-gc Data Of Kerogensupporting
confidence: 82%
“…However, this method should be used with caution, because mature amorphous organic matter (AOM) does not fluoresce (Durand, 1980 and references therein). Therefore, we examined the identification of AOMs on the basis of both the fluorescence and the morphology under transmitted light microscope as reported by Tyson (1995), Boussafir et al (1995), Tribovillard et al (2001), Sawada (2006), and Ercegovac and Kostic (2006). The Table 2 show photomicrographs of kerogens separated from sedimentary rocks and their palynofacies compositions from the Changhsing to Yinkeng Formations, respectively.…”
Section: Palynofacies Analysismentioning
confidence: 99%
See 3 more Smart Citations